2020
DOI: 10.1101/2020.02.12.20022418
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ACE2 Expression in Kidney and Testis May Cause Kidney and Testis Damage After 2019-nCoV Infection

Abstract: In December 2019 and January 2020, novel coronavirus (2019-nCoV) -infected pneumonia (NCIP) occurred in Wuhan, and has already posed a serious threat to public health. ACE2 (Angiotensin Converting Enzyme 2) has been shown to be one of the major receptors that mediate the entry of 2019-nCoV into human cells, which also happens in severe acute respiratory syndrome coronavirus (SARS). Several researches have indicated that some patients have abnormal renal function or even kidney damage in addition to injury in r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
368
1
13

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(388 citation statements)
references
References 20 publications
6
368
1
13
Order By: Relevance
“…thus, we should consider the possibility of the virus infecting these cells, which is supported by the significant decrease in the platelet counts in both grade 2-group and grade 3-group COVID-19 patients and the reduced count of trilineage in the bone marrow . [14][15][16] In correspondence with pathological findings, we also All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 99%
“…thus, we should consider the possibility of the virus infecting these cells, which is supported by the significant decrease in the platelet counts in both grade 2-group and grade 3-group COVID-19 patients and the reduced count of trilineage in the bone marrow . [14][15][16] In correspondence with pathological findings, we also All rights reserved. No reuse allowed without permission.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the virus might affect renal tubular cells and testicular cells due to the high expression of ACE2, which is often found in the membranes of the lungs, kidneys cells and cells in seminiferous ducts of the testis. Consequently, 19-nCoV may directly bind to such ACE2 bearing cells and J o u r n a l P r e -p r o o f Journal Pre-proof damage the kidney and testicular tissue of patients [44]. Nevertheless, incomplete evidence is presented concerning the involvement of reproductive organs in patients infected with 2019-nCoV.…”
Section: Symptomsmentioning
confidence: 99%
“…However, the ACE2 receptor is not only expressed in the respiratory organs. It has been reported that, by using the RNA-seq method to express ACE2 receptors in human tissues, the number of ACE2 receptors expressed in the gastrointestinal tract (high in esophagus, small intestine, and colon, but low in stomach), kidneys, and testes is nearly 100 times higher than that in the lung [15], suggesting that these tissues may also be the target organs for SARS-CoV-2 invasion. It may explain why some patients with COVID-19 developed other system injuries clinically besides respiratory system injuries.…”
Section: The Pathogenic Mechanisms Of Covid-19mentioning
confidence: 99%